A CROSS-SECTIONAL STUDY OF FATALITIES RESULTING FROM SNAKE BITES REPORTED TO SCB MEDICAL COLLEGE AND HOSPITAL, CUTTACK, ODISHA - Sahu, Geeta; Jena, Mamata; Prasad, C.S Debi; Jena, Soumya Ranjan (Journal of Forensic Medicine and Toxicology, 2025)
Introduction: Snakebite is a serious issue in India affecting rural dwellers. India has the unfortunate distinction of having the highest number of snakebite cases, leading to a staggering number of recorded fatalities worldwide. The species variation is highest in this region. Aims and Objective: The study aims to establish the prevalence of species involved in snakebite cases admitted to the hospital and to analyze the demographic profile of medico-legal autopsies conducted on snakebite victims at the mortuary of SCB Medical College, Cuttack, from September 2018 to August 2021. Methods: A self-designed questionnaire was prepared to obtain data on victims. Statistical analysis was performed using SPSS Statistical software. The sample consisted of 333 fatal cases received during the period. Results: Middle age group people (41–50 years) were most affected. Most of the victims were dependent women and children. Night time during sleep was the most suitable period for snakes to attack. Neurotoxic envenomation death was found to be more prevalent especially due to krait bite omited. Our study identified rural residency and indoor encounters with snake species as significant risk factors for snakebite. In most cases, there was a time gap of 1 to 6 hours between snake bites and admission in hospitals. However, in some instances, this gap extended even further, ranging from 12 to 24 hours. Discussion: The study concluded that the delay in treatment led to a high number of deaths. Therefore, early admission to the hospital and timely detection and treatment strategies could significantly reduce snakebite mortality.
Keywords: Snakebite; Victims; treatment